Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jgc4.1160
|View full text |Cite
|
Sign up to set email alerts
|

Examining genetic counselors’ implicit attitudes toward disability

Abstract: Genetic counselors have a unique role in healthcare that requires a balance between being a patient educator and patient advocate when discussing disability. This study aimed to determine genetic counselors’ implicit attitudes toward disability, and identify what factors affect these implicit attitudes. Case scenarios involving disability were used to examine hypothetical estimates of time spent on different topics within a genetic counseling session. Implicit attitudes were measured using the validated Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…The prevalence of pro-White bias among recent GC graduates was also lower than other reports of bias towards other majority populations among genetic counselors (Gould et al, 2019;Lowe et al, 2020;Nathan et al, 2019)…”
Section: Comfortability Interaction and Favorabilitycontrasting
confidence: 58%
See 2 more Smart Citations
“…The prevalence of pro-White bias among recent GC graduates was also lower than other reports of bias towards other majority populations among genetic counselors (Gould et al, 2019;Lowe et al, 2020;Nathan et al, 2019)…”
Section: Comfortability Interaction and Favorabilitycontrasting
confidence: 58%
“…A 2014 study of third‐year medical students showed that 65% of respondents demonstrated implicit bias towards people of similar demographic groups as themselves (Gonzalez et al., 2014). The prevalence of pro‐White bias among recent GC graduates was also lower than other reports of bias towards other majority populations among genetic counselors (Gould et al., 2019; Lowe et al., 2020; Nathan et al., 2019). Specifically, Lowe et al reported that 77% of practicing genetic counselors involved in their study demonstrated bias favoring White individuals.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Differences in implicit bias between cultural groups were also suggested by findings of studies that investigated racial differences (Coleman et al, 2015; Friedman, 2019; Harder et al, 2019; Jiang et al, 2021; Thomas et al, 2014; VanPuymbrouck et al, 2020); however, such studies compared racial groups within a specified country rather than between countries. Furthermore, samples of healthcare professionals also yielded higher D -scores for general disability (Aaberg, 2012; Archambault et al, 2008; Gould et al, 2019). When comparing implicit attitude results of studies that used Project Implicit data, while all were in the moderate negative implicit attitude range, the subset sample of healthcare professionals had the highest reported D -score (VanPuymbrouck et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…These include, for example, arguments that the practice of prenatal testing invariably judges certain disabled lives to be not worthy or less worthy of living or that its effect, regardless of questions of judgment, is the prevention of certain people with disabilities from coming into being. 1 Importantly, calls for greater attention to the complexity of disability as well as calls for greater incorporation of the experiential testimony of various disability communities have for many years now also become increasingly common from inside the practice of prenatal genetic counseling (Farrelly et al 2012;Sanborn and Patterson 2014;Madeo et al 2011;Gould et al 2019;Boardman 2020). Whether coming from inside or outside, these calls often assume that genetic counselors' responsibilities to disability communities revolve around dialogue, understanding, and representation.…”
mentioning
confidence: 99%